PENGARUH KEPERCAYAAN, KEPUASAN TERHADAP LOYALITAS DENGAN KEPEMIMPINAN PENGURUS SEBAGAI VARIABEL MODERATING (Studi Kasus BMT Bahtera, BTM di Pekalongan dan Kospin Jasa Syariah Cabang Pekalongan) (Jurnal Penelitian, 2013)
This study aimed to determine the effect of trust, satisfaction to the customers' loyalty that moderated by leadership of the board as a moderating variable. A total of 100 questionnaires with closed answer using a Likert scale were spread to 100 customers BTM Wiradesa, BMT Bahtera and Kospin Jasa Syariah in Pekalongan to answer the problem. The results showed that trust, satisfaction and leadership of the board, respectively had positive and significant effect on customers' loyalty. Meanwhile, the leadership of the board as a moderating variable is also positive and significant effect on customer loyalty.
Keywords: kepercayaan, kepuasan, kepemimpinan, loyalitas